Evaluation of Risk Management of the Housing Fund Program (FP) Zero Rupiah for the DKI Jakarta Provincial Government Case Study on the Housing Fund Management Unit - Poppy Oktaviandry S; Desi Adhariani (Green Publisher Indonesia, 2025)
This study aims to evaluate the implementation of the risk management process in the Zero Rupiah Housing Fund Program intended for Low-Income Communities with DKI Jakarta Provincial Governor Regulation Number 122 of 2020 and the ISO 31000: 2018 conceptual framework as a reference concept for best practice in the Housing Fund Management Unit that implements the Regional Public Service Agency Financial Management Pattern. The research method used is qualitative with a case study approach. This research uses a triangulation method that combines various research instruments simultaneously to strengthen the results obtained from all types of data, including document analysis and interviews, to be analysed using the thematic analysis method. In this study, the risk management process in implementing the Zero Rupiah DP Program is evaluated, starting from the program planning process to the monitoring and evaluation process of program implementation. The results of this study show that UPDP has not established a risk appetite, and the risk management process in the Zero Rupiah DP Program is still at the risk evaluation stage. This study provides recommendations regarding implementing risk management that refer to the reference standards as best practice in the risk management process.